Adoption of returnable packaging depends on price, deposit, and material, with spillovers from recycling and reuse - Thompson, Bethan; Akaichi, Faical; Toma, Luiza (Frontiers in Sustainability, 2026)
IntroductionPolicies to reduce packaging waste increasingly promote reusable formats, yet evidence on consumer demand for returnable packaging remains limited. This study examines preferences, willingness to pay, and behavioural spillovers in the adoption of returnable packaging for food and non-food products in the UK.MethodsWe conducted a nationally representative discrete choice experiment across two product categories: a food item (flaked corn cereal) and a non-food household cleaner. Alternatives varied by price, deposit level, number of prior uses, container material (glass versus plastic), and return location. Multinomial logit and latent class models were used to estimate preferences, willingness to pay, and heterogeneity in acceptance. Secondary analysis linked stated choices to self-reported recycling and reuse behaviours, self-efficacy, and environmental concern to test for behavioural spillovers and psychological influences.ResultsHigher prices and deposit levels reduced the likelihood of selecting returnable options, while glass was generally preferred to plastic. Prior uses influenced acceptance only for the cleaner, and return location had little effect in either category. Latent class models consistently identified two segments: cost-conscious sceptics, who are typically older, more price-sensitive, and more likely to reject returnables; and open-minded adopters, who are younger, less price-sensitive, and already more engaged in refill behaviours. Secondary analysis indicates positive behavioural spillovers: individuals reporting stronger engagement in recycling and reuse behaviours were more likely to adopt returnable packaging. By contrast, self-efficacy and environmental concern played a weaker and more context-specific role, particularly in the food category.DiscussionThe findings suggest that experience with circular practices offers a stronger foundation for adoption of returnable packaging than general pro-environmental attitudes alone. Deposit levels must be carefully calibrated to avoid deterring uptake, and material choices should be aligned with product contexts. Adoption strategies may be improved by targeting consumer segments, prioritising those already practising reuse and recycling. To our knowledge, this is the first discrete choice experiment to quantify willingness to pay for returnable packaging across categories while explicitly testing behavioural spillovers. The study demonstrates that spillover operates through transferable competencies rather than system-specific familiarity, that psychological constructs predict preferences context-dependently, and that established circular practices outperform attitudinal measures in predicting acceptance, supporting behaviour-based intervention strategies.